Melatonin Protects Against Mdivi-1-Induced Abnormal Spindle Assembly and Mitochondrial Superoxide Production During Porcine Oocyte Maturation - Yang, Seul-Gi; Joe, Seung-Yeon; Bae, Jin-Wook; Heo, Gyeong-Deok; Park, Hyo-Jin; Koo, Deog-Bon (Frontiers in Cell and Developmental Biology, 2021)
Mitochondrial division inhibitor 1 (Mdivi-1) reportedly provides a close connection between oocyte maturation and mitochondrial function in pigs. N-acetyl-5-methoxy-tryptamine (melatonin) is known to be a representative antioxidant with the ability to rehabilitate meiotic maturation of porcine oocytes. However, the ability of melatonin to recover Mdivi-1-mediated disruption of spindle formation during meiotic maturation of porcine oocytes during in vitro maturation (IVM) has not been studied. Here, we first investigated changes in mitochondrial length, such as fragmentation and elongation form, in porcine maturated oocytes during IVM. Mature oocytes require appropriate mitochondrial fission for porcine oocyte maturation. We identified a dose-dependent reduction in meiotic maturation in porcine oocytes following Mdivi-1 treatment (50, 75, and 100 M). We also confirmed changes in mitochondrial fission protein levels (pDRP1-Ser616 and DRP1), mitochondrial membrane potential, and ATP production in 75 μM Mdivi-1-treated oocytes. As expected, Mdivi-1 significantly reduced mitochondrial function and DRP1 protein levels and increased spindle abnormalities in porcine oocytes. In addition, we confirmed that melatonin restores abnormal spindle assembly and reduces meiotic maturation rates by Mdivi-1 during porcine oocyte maturation. Interestingly, the expression levels of genes that reduce DNA damage and improve tubulin formation were enhanced during porcine meiotic maturation. Taken together, these results suggest that melatonin has direct beneficial effects on meiotic maturation through tubulin formation factors during porcine oocyte maturation.